Keragaman konsumsi pangan remaja putri di wilayah perdesaan dan perkotaan Provinsi Bali - Utami, Ni Wayan Arya; Ani, Luh Seri (Poltekkes Kemenkes Aceh, 2024)
Background: Malnutrition is caused by insufficient nutritional intake that can be assessed from the dietary diversity. Dietary diversity can be influenced by socio demographic characteristic and living area, rural and urban. Adolescent girls are at risk of malnutrition due to nutritional intake factors and infectious diseases.Objectives: To determine the differences in demographic characteristics and food diversity between rural and urban areas and the correlation between demographic characteristics and food diversity between demographic characteristics and food diversity. Methods: The study a descriptive cross-sectional study was conducted on 110 respondents selected by multistage random sampling in Denpasar City and Karangasem Regency, Bali Province. Data were collected through interviews using a structured questionnaire and then analyzed univariately, bivariately with simple linear regression test and multivariably with multiple linear regression test.Results: The results showed significant differences between rural and urban areas based on age, education, occupation, family income, food diversity, consumption of green leafy vegetables group; meat, poultry, fish group; egg group and milk group (p-value <0,05). Bivariable tests showed a significant influence of geographical factors, education and family income on food diversity and geographical factor as a determinant of food diversity.Conclusion: It is concluded that the residence factor is the most dominant factor affecting food diversity